1991
DOI: 10.1115/1.2895413
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Prediction for the Proximal Femur Using Finite Element Models: Part II—Nonlinear Analysis

Abstract: In Part I we reported the results of linear finite element models of the proximal femur generated using geometric and constitutive data collected with quantitative computed tomography. These models demonstrated excellent agreement with in vitro studies when used to predict ultimate failure loads. In Part II, we report our extension of those finite element models to include nonlinear behavior of the trabecular and cortical bone. A highly nonlinear material law, originally designed for representing concrete, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 0 publications
0
56
0
1
Order By: Relevance
“…These variables direct the propagation of yielded material and the decrement of the elastic stiffness [29]. The damage plasticity model represents the inelastic behaviour of the bone by combining isotropic damaged elasticity with isotropic tensile and compressive plasticity.…”
Section: Methodsmentioning
confidence: 99%
“…These variables direct the propagation of yielded material and the decrement of the elastic stiffness [29]. The damage plasticity model represents the inelastic behaviour of the bone by combining isotropic damaged elasticity with isotropic tensile and compressive plasticity.…”
Section: Methodsmentioning
confidence: 99%
“…As CT attenuations only provide a scalar value at each point, many studies assume isotropic elasticity (164)(165)(166)(167)(168)(169), although anisotropic material properties have also been implemented using information within the voxel (170). The elastic moduli for early isotropic models have been homogeneous (171)(172)(173), but more recent studies have used inhomogeneous materials (8,164,165,170,174-178) as they have been found to be more accurate than the models using homogeneous material properties (9,179,180).…”
Section: The Finite Element Methodsmentioning
confidence: 99%
“…Lotz et al investigated the predictive value for fracture load of linear (Lotz et al 1991a) and nonlinear (Lotz et al 1991b) models. In addition, they studied the predictive value for femoral fracture load of stress-and strain-based theories in linear models (Lotz et al 1991a).…”
Section: (A ) Fe Meshmentioning
confidence: 99%